Sulforaphane-Mediated Nrf2 Activation Prevents Radiation-Induced Skin Injury through Inhibiting the Oxidative-Stress-Activated DNA Damage and NLRP3 Inflammasome - Jinlong Wei; Qin Zhao; Yuyu Zhang; Weiyan Shi; Huanhuan Wang; Zhuangzhuang Zheng; Lingbin Meng; Ying Xin; Xin Jiang (MDPI AG, 2021)
This article mainly observed the protective effect of sulforaphane (SFN) on radiation-induced skin injury (RISI). In addition, we will discuss the mechanism of SFN's protection on RISI. The RISI model was established by the irradiation of the left thigh under intravenous anesthesia. Thirty-two C57/BL6 mice were randomly divided into control group (CON), SFN group, irradiation (IR) group, and IR plus SFN (IR/SFN) group. At eight weeks after irradiation, the morphological changes of mouse skin tissues were detected by H&E staining. Then, the oxidative stress and inflammatory response indexes in mouse skin tissues, as well as the expression of Nrf2 and its downstream antioxidant genes, were evaluated by ELISA, real-time PCR, and Western blotting. The H&E staining showed the hyperplasia of fibrous tissue in the mouse dermis and hypodermis of the IR group. Western blotting and ELISA results showed that the inflammasome of NLRP3, caspase-1, and IL-1β, as well as oxidative stress damage indicators ROS, 4-HNE, and 3-NT, in the skin tissues of mice in the IR group were significantly higher than those in the control group (p < 0.05). However, the above pathological changes declined sharply after SFN treatment (p < 0.05). In addition, the expressions of Nrf2 and its regulated antioxidant enzymes, including CAT and HO-1, were higher in the skin tissues of SFN and IR/SFN groups, but lower in the control and IR groups (p < 0.05). SFN may be able to suppress the oxidative stress by upregulating the expression and function of Nrf2, and subsequently inhibiting the activation of NLRP3 inflammasome and DNA damage, so as to prevent and alleviate the RISI.